T‐cell memory in tissues. Issue 6 (29th April 2021) - van Gisbergen, Klaas P. J. M.; Zens, Kyra D.; Münz, Christian
Abstract: Immunological memory equips our immune system to respond faster and more effectively against reinfections. This acquired immunity was originally attributed to long‐lived, memory T and B cells with body wide access to peripheral and secondary lymphoid tissues. In recent years, it has been realized that both innate and adaptive immunity to a large degree depends on resident immune cells that act locally in barrier tissues including tissue‐resident memory T cells (Trm). Here, we will discuss the phenotype of these Trm in mice and humans, the tissues and niches that support them, and their function, plasticity, and transcriptional control. Their unique properties enable Trm to achieve long‐lived immunological memory that can be deposited in nearly every organ in response to acute and persistent infection, and in response to cancer. However, Trm may also induce substantial immunopathology in allergic and autoimmune disease if their actions remain unchecked. Therefore, inhibitory and activating stimuli appear to balance the actions of Trm to ensure rapid proinflammatory responses upon infection and to prevent damage to host tissues under steady state conditions. Abstract : In addition to circulating memory lymphocytes, especially barrier tissues are equipped with tissue resident memory cells including T cells. Even so these carry inhibitory receptors of exhaustion, they are an exquisite first line of defense against malignant cells and infections including those by persistent viruses.